Exo70E2 is essential for exocyst subunit recruitment and EXPO formation in both plants and animals - Ding, Yu (The American Society for Cell Biology, 2014)
In contrast to a single copy of Exo70 in yeast and mammals, the Arabidopsis genome contains 23 paralogues of Exo70 (AtExo70). Using AtExo70E2 and its GFP fusion as probes, we recently identified a novel double-membrane organelle termed exocyst-positive organelle (EXPO) that mediates an unconventional protein secretion in plant cells. Here we further demonstrate that AtExo70E2 is essential for exocyst subunit recruitment and for EXPO formation in both plants and animals. By performing transient expression in Arabidopsis protoplasts, we established that a number of exocyst subunits (especially the members of the Sec family) are unable to be recruited to EXPO in the absence of AtExo70E2. The paralogue AtExo70A1 is unable to substitute for AtExo70E2 in this regard. Fluorescence resonance energy transfer assay and bimolecular fluorescence complementation analyses confirm the interaction between AtExo70E2 and Sec6 and Sec10. AtExo70E2, but not its yeast counterpart, is also capable of inducing EXPO formation in an animal cell line (HEK293A cells). Electron microscopy confirms the presence of double-membraned, EXPO-like structures in HEK293A cells expressing AtExo70E2. Inversely, neither human nor yeast Exo70 homologues cause the formation of EXPO in Arabidopsis protoplasts. These results point to a specific and crucial role for AtExo70E2 in EXPO formation.